Analisis Keselamatan Transportasi Pelayaran Rakyat - Malisan, Johny (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Population of tradi.tional shipping tends to decrease due to numy accidents happen that should beanalyzed, particularly relating to technical and non-teclmical •cts which are suppofed to influence itssafehj perftmnance. The teclmical aspects to be revien d include construction strength and stabilihj ofship. Mernwhile non-technical aspects to be revielwl are including qxrational management of ships onland and rompetence of crews. Another is safety management in order to realize